Character Education as the Main Foundation of Quality Youth in Wakap Village, Bantarkalong Sub-District Tasikmalaya District - Sahrona Harahap; Aim Abdul Karim (Dinamika: Jurnal Pengabdian kepada Masyarakat, 2024)
The degradation of the character of young people in this era, both urban and urban, is a complex influence of various factors. The study aims to analyze and address the character problems of young people in Wakap Village. The steps taken include the development of a character education curriculum, the implementation of character education, the active involvement of parents and families, and the strengthening of local values. The research also discusses the potential of tourism and local intelligence as an effort to preserve identity and create sustainable development. The research uses a descriptive qualitative approach with the identification of stakeholders through interviews and observations. The results of the research show that the development of character education curriculum that takes into account local values succeeds in improving the understanding and internalization of positive character in young people Village Wakap. Implementing character education involves the bonding of parents, teachers, and the community, creating an environment that supports the formation of a positive character. The anti-bullying program with parents and the involvement of local figures as inspirers also had a positive impact. Strengthening local values in Wakap Village involves introducing local history and culture, cultural activities, and community involvement. Tourism potential and local wisdom can be the basis for sustainable development. These measures together create an educational environment that supports positive character growth and reduces the incidence of bullying. The implications of this research include a deep understanding of public involvement in character education as well as the urgency of applying local values in the context of formal education. Hopefully these findings can be a reference for similar curriculum development in other villages or communities.